Governance and social responsibility : international perspectives - Aras, Guler; Crowther, David (Palgrave Macmillan, 2012)
A rigorous introduction to CSR which explores the variety of perspectives and debates, incorporating an international orientation throughout. The text will give students a firm underpinning theory in which to understand the key debates and issues